Menelusuri Perbedaan Ilustrasi Keris Nagasasra dalam Naskah Keris ll dengan Pakem Dhapur Keris - Nadhira, Aliffia Marsha; Wulandari, Arsanti; Raharja, R. Bima Slamet (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2024)
Keris Nagasasra is one of the well-known keris in Java Island. It is said that this ‘keris’ was used as a replacement for the damaged Keris Kyai Condhong Campur from Majapahit Kingdom. The stories surrounding this ‘keris’ are not only spread through oral literature, but also recorded in ancient manuscripts. One of the manuscripts containing story of the creation of Keris Nagasasra is Naskah Keris II collection of Sonobudoyo Museum Yogyakarta. The manuscript also presents an illustration of Keris Nagasasra drawn in watercolor. With multimodal approach initiated by Gunther Kress and Theo van Leeuwen, it can be seen that the illustration of Keris Nagasasra in Naskah Keris II is incomplete when compared to the pakem of dhapur ‘keris’ which was agreed upon keris community. Since the initiator or copyist of Naskah Keris II is difficult to trace, the researchers offer three possibilities for the difference in illustrations to occur. First, the illustrator is someone who does not understand the dhapur ‘keris’ standard because he/she made a keris illustration that is not in accordance with the standard. Second, on the contrary, the illustrator was very knowledgeable about the pakem of dhapur ‘keris’, which is considered sinengker so it should not be known to the public. Third, there are limited resources, such as ink and paint, in making the illustrations of Naskah Keris II so that ‘keris’ illustrations are not drawn according to the standard. === Keris Nagasasra merupakan salah satu keris yang termasyhur di Pulau Jawa. Konon keris ini dijadikan sebagai pengganti dari Keris Kyai Condhong Campur milik Kerajaan Majapahit yang rusak. Kisah-kisah yang melingkupi keris ini tidak hanya tersebar melalui cerita lisan dari mulut ke mulut, tetapi juga dimuat dalam manuskrip kuno. Salah satu manuskrip yang memuat kisah penciptaan Keris Nagasasra adalah Naskah Keris II koleksi Perpustakaan Museum Sonobudoyo Yogyakarta. Dalam naskah tersebut disajikan pula ilustrasi dari Keris Nagasasra yang digoreskan dengan cat air. Dengan pendekatan multimodal yang digagas oleh Gunther Kress dan Theo van Leeuwen, dapat diketahui bahwa terdapat perbedaan ilustrasi Keris Nagasasra dalam Naskah Keris II dengan pakem dhapur keris yang disepakati masyarakat perkerisan. Akibat dari pemrakarsa dan penyalin naskah Naskah Keris II yang sulit dilacak, maka peneliti menawarkan tiga kemungkinan sebab perbedaan ilustrasi terjadi. Pertama, ilustrator merupakan seseorang yang kurang paham mengenai pakem dhapur keris karena membuat ilustrasi keris yang tidak sesuai pakem. Kedua, malah sebaliknya, ilustrator sangat paham mengenai pakem dhapur keris yang dianggap sinengker sehingga tidak boleh diketahui khalayak umum. Ketiga, adanya keterbatasan sumber daya, seperti tinta dan cat, dalam pembuatan ilustrasi Naskah Keris II sehingga ilustrasi keris digambar tidak sesuai dengan aslinya.